Palazzo Querini Stampalia, Detaljmodell - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2022)
Carlo Scarpa is the architect behind the modern renovation of the garden and part of the ground floor for the Venetian institution Querini Stampalia. Scarpa is admired for his balanced combination of old and new elements, as well as on a great workmanship of the materials. The focus of this model is on the way Scarpa let the sea enter the building and connect to a sculptural indoor stairway. The model captures the reflectiveness of the water and also todays problem of motorboats tearing through the channel and causing ruinous swells.
Palazzo Querini Stampalia model